MOBILE LEARNING BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN PAI DI MAN 2 YOGYAKARTA - Fauzan, Tsaaniyatush Shoolihah (Jurnal Tarbiyah Almuslim, 2024)
This study aims to analyze the implementation of Android-based mobile learning as a learning media for Islamic Education (PAI) at MAN 2 Yogyakarta. With rapid technological advancements, the use of mobile devices such as smartphones and tablets is increasingly widespread among students. This research explores the opportunities of utilizing Android applications as interactive and engaging learning media for students. The research method employed is a qualitative approach, utilizing data collection techniques through observation, interviews, and document analysis. The research subjects involve PAI teachers, students, and relevant stakeholders at MAN 2 Yogyakarta. The results indicate that the implementation of Android-based mobile learning can enhance students' interest and motivation in PAI subjects. The Android applications used present learning materials in attractive multimedia formats, accompanied by quizzes, exercises, and online discussion features. Moreover, mobile learning enables flexible learning where students can access materials anytime and anywhere. However, there are challenges in implementing mobile learning, such as limited internet infrastructure in schools and issues related to students' distraction from smartphone usage, affecting their concentration during learning. The study provides recommendations to optimize the use of mobile learning by providing guidelines and training for teachers and involving parents in monitoring the use of mobile devices.